Cerebral Pathology and Cognition in Diabetes: The Merits of Multiparametric Neuroimaging - van Bussel, Frank C. G.; Backes, Walter H.; Hofman, Paul A. M.; van Oostenbrugge, Robert J.; van Boxtel, Martin P. J.; Verhey, Frans R. J.; Steinbusch, Harry W. M.; Schram, Miranda T.; Stehouwer, Coen D. A.; Wildberger, Joachim E.; Jansen, Jacobus F. A. (Frontiers in Neuroscience, 2017)
Type 2 diabetes mellitus is associated with accelerated cognitive decline and various cerebral abnormalities visible on MRI. The exact pathophysiological mechanisms underlying cognitive decline in diabetes still remain to be elucidated. In addition to conventional images, MRI offers a versatile set of novel contrasts, including blood perfusion, neuronal function, white matter microstructure, and metabolic function. These more-advanced multiparametric MRI contrasts and the pertaining parameters are able to reveal abnormalities in type 2 diabetes, which may be related to cognitive decline. To further elucidate the nature of the link between diabetes, cognitive decline, and brain abnormalities, and changes over time thereof, biomarkers are needed which can be provided by advanced MRI techniques. This review summarizes to what extent MRI, especially advanced multiparametric techniques, can elucidate the underlying neuronal substrate that reflects the cognitive decline in type 2 diabetes.